Pelatihan Keterampilan Merias Wajah Jenis Korektif Bagi Tim Penari Oglek Tempe Kampung Sanan Malang - Suprihatin, E. Wara; Sumarwahyudi, Sumarwahyudi; Hidajat, Robby; Widyawati, Ika Wahyu (Civiliza Publishing, 2024)
Kampung Sanan has been designated as a tourist destination for small, household-based industries with a mainstay product, tempe chips. Data on tourist visits in 2023 will average 250 people/month. Tourists are met at the entrance gate of Sanan Village, by the Tour Guide team and greeted with a typical Sanan welcoming dance, namely the Oglek Tempe Dance. There is a problem that is an obstacle for dancers because they do not have their own make-up equipment nor do they have the skills to apply make-up independently for corrective stage make-up when they want to dance. This causes it to be ineffective and uneconomical because when they want to dance they have to go to the salon or bring in a make-up artist. The aim of the service activity is to provide corrective stage make-up training for the Oglek Tempe dance team so that they are skilled at applying make-up independently. The training method applies demonstration methods and guided practice methods, while for enrichment tutorials are provided in video form. From the results of the activity evaluation, 5 participants were not yet skilled, 10 people were skilled and 5 people were quite skilled.